Perlindungan Hukum Bagi Konsumen Bunda Laundry Atas Kelalaian Pelaku Usaha Yang Mengakibatkan Kerugian Pada Konsumen - I Wayan Pande Eka Trisna; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2025)
Consumer protection is an important aspect of running a sustainable business. Legal balance between consumers and producers is the key to preventing losses to consumers. This research aims to examine the legal protection for Bunda Laundry consumers who suffer losses due to the negligence of business actors. Law Number 8 Year 1999 on Consumer Protection is (1) How the legal basis that covers laundry service users. The formulation of the research problem includes questions about legal protection for consumers of Bunda Laundry? and (2) How to resolve the negligence of business actors that result in losses?. The type of research used is Empirical Law with a sociological approach, statutory approach, and conceptual approach. Data sources involve primary legal materials from the Constitution of the Republic of Indonesia, as well as interviews with owners, customers, and employees of Bunda Laundry. Data analysis was conducted by assembling data, clarifying, analyzing, and interpreting data to find relevant patterns and relationships. This research was conducted at Bunda Laundry on Jalan Lettu Anom Kawan Bangli, The results of the study are expected to contribute to the understanding of consumer legal protection in the laundry service business.